The role of modern technology in transforming luxury services into basic services in the tourism sector - Hayder Salih Hadi; ALI yousif darjal (Peerian Journals Publishing, 2025)
This research confirmed that examining the perceptions of tourism and hotel managers in Iraq regarding the role of modern technology in transforming luxury services into essential services in the tourism sector. Empirical .evidence strongly supports .the key role of cybersecurity and data protection in transforming luxury services into essential services, while the impact of digital marketing and artificial intelligence, despite their statistical significance, appears marginal. Travelers' digital experience does not significantly influence the transformation of luxury services into essential services, suggesting a more complex. relationship than initially thought. This research makes an. innovative contribution to understanding the relationship between digital transformation in tourism operations in Iraq, highlighting specific ways in which digital technologies can sustain the transformation of luxury services into essential services. Its importance lies in identifying practical. steps hotel managers can. take to harness the potential .of technological innovation, which contributes not only to improving the ability to change perceptions, but also. to promoting technology as .a key component of .business strategy in the .tourism sector.
Keywords: Technology; Services; Digital Marketing